Data on the experimental manipulation of local population density and the discovery of novel food patches in woodland birds - Beck, K; Crofts, S; McMahon, K; Firth, J; Cole, E; Sheldon, B (University of Oxford, 2022)
This dataset contains information about local population densities of great tits, blue tits, marsh tits and nuthatches from a manipulation experiment. The time, location and bird species were recorded using a (Passive Integrated Transponder) PIT tag attached to each bird and the information recorded using a (Radio Frequency Identification) RFID antenna within the feeder. Population density was manipulated by programming automated feeders to only open for a specific set of individuals (creating low- and high-density treatments). Local population densities were recorded using automated bird feeders at six experimental and two control sites prior to and during the manipulation. In addition, we collected recordings of great tits, blue tits, marsh tits and nuthatches discovering novel food patches in relation to the manipulated local population densities. Prior to and during the density manipulation experiment, novel feeders were placed at random locations and the discovery of these was recorded using a Passive Integrated Transponder (PIT) tag attached to each bird and the information recorded using a Radio Frequency Identification (RFID) antenna within the feeder. The experiments took place in Wytham woods, Oxfordshire, UK between January and March 2021, as part of a study on the effects of ecological factors on social structure and information transmission. The work was supported by the Natural Environment Research Council (Grant NE/S010335/1), The ecology of behavioural contagion in natural systems). See supporting documentation for more information.